2023
DOI: 10.3892/ijo.2023.5501
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific GPC3/PD‑1 CAR‑T cells for the treatment of HCC

Abstract: Constantly stimulated by the tumor microenvironment (TME), programmed death 1 (PD-1) is elevated, and it interacts with PD ligand 1 (PD-L1), rendering chimeric antigen receptor (CAR)-T cells dysfunctional. Hence, CAR-T cells immune to PD-1-induced immunosuppression were constructed to improve the function of CAR-T cells in hepatocellular carcinoma (HCC). Double-target CAR-T cells, targeting glypican-3 (GPC3) [a tumour-associated antigen (TAA)] and hindering PD-1-PD-L1 binding, were established. The expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Double-target CAR T cells against GPC3 and PD-1 were evaluated and the results showed limited PD-1-PD-L1 binding and sustained cytotoxicity to PD-L1+ HCC cells [ 102 ]. The low expression of inhibitory receptors in double-target CAR T cells facilitated the suppression of tumor and extended survival in PD-L1+ HCC models compared to their single-target cells [ 102 ]. Jiang et al established three patient-derived xenograft (PDX) models of HCC with GPC3-positive expression [ 103 ].…”
Section: Car T Cell Therapy Targets For Hccmentioning
confidence: 99%
“…Double-target CAR T cells against GPC3 and PD-1 were evaluated and the results showed limited PD-1-PD-L1 binding and sustained cytotoxicity to PD-L1+ HCC cells [ 102 ]. The low expression of inhibitory receptors in double-target CAR T cells facilitated the suppression of tumor and extended survival in PD-L1+ HCC models compared to their single-target cells [ 102 ]. Jiang et al established three patient-derived xenograft (PDX) models of HCC with GPC3-positive expression [ 103 ].…”
Section: Car T Cell Therapy Targets For Hccmentioning
confidence: 99%
“…Two sequential phase 1 clinical trials (ClinicalTrials.gov, NCT02395250, ClinicalTrials.gov, NCT03146234) have observed antitumor activity of CAR‐GPC3 T cells in HCC patients and demonstrate that the treatment is feasible with preliminary safety 295 . Li et al 296 . established dual‐target CAR‐T cells that target GPC‐3 and PD‐1 and showed stronger tumor inhibitory effect on HCC compared with single‐target CAR‐T cells.…”
Section: Immunotherapy In Hccmentioning
confidence: 99%
“…294 Two sequential phase 1 clinical trials (ClinicalTrials.gov, NCT02395250, ClinicalTrials.gov, NCT03146234) have observed antitumor activity of CAR-GPC3 T cells in HCC patients and demonstrate that the treatment is feasible with preliminary safety. 295 Li et al 296 established dual-target CAR-T cells that target GPC-3 and PD-1 and showed stronger tumor inhibitory effect on HCC compared with single-target CAR-T cells. In addition, disrupting PD-1 expression through Cas9/CRISPR can improve the anti-HCC effect of CAR-T cells in vitro and in vivo, suggesting the potential advantages of CAR-T cells combined with ICIs in controlling solid tumors.…”
Section: Icis Combined With Targeted Drugsmentioning
confidence: 99%
“…A novel double-target CAR-T cell therapy has been developed, recognizing GPC3 (a protein upregulated in HCC) and inhibiting PD-1, demonstrating superior therapeutic effects on HCC compared to single-target CAR-T cells. These double-target CAR-T cells showed enhanced persistence, limited inhibitory receptor expression, and potent resistance against tumor cells [76]. In a phase I clinical trial focusing on Glypican-3 (GPC3), a significant HCC-associated antigen, as a promising target for heavily treated HCC patients CT017 CAR T cells co-expressing CAR-GPC3 and RUNX3 were engineered to induce CD8+ T-cell infiltration within the cancer microenvironment.…”
Section: Chimeric Antigen Receptor (Car)-t Cell Therapymentioning
confidence: 99%
“…The trial demonstrated a manageable safety profile, with all patients experiencing cytokine release syndrome (CRS) primarily at grades 2 and 3, which resolved post-treatment. Notably, one patient achieved a partial response, and two had stable disease, resulting in a 16.7% objective response rate and a 50% disease control rate [76][77][78][79].…”
Section: Chimeric Antigen Receptor (Car)-t Cell Therapymentioning
confidence: 99%